Improving the effectiveness of collective action: sharing experiences from community forestry in Nepal - Acharya, Krishna P.; Gentle, Popular (International Food Policy Research Institute, 2006)
The forest management strategy of Nepal is based on people’s participation, which is known as community forestry. This approach was formally introduced in 1978 to encourage active participation of local people in forest management activities as a means to improve their livelihoods. Under the community forestry structure, local people make decisions regarding forest management, utilization and distribution of benefits from a forest; they are organized as a Community Forest User Group. Presently about 1.2 million hectares of forest is under the control of about 14,000 Community Forest User Groups. It has received highest priority within the forestry sector and is one of the most successful development initiatives in Nepal. However, emerging evidence indicates that forest user groups have excluded rather than included women’s participation in their activities. This paper is based on the findings from six forest users groups implementing a program aimed at strengthening governance at the local level through increased women’s participation and increased advocacy skills and capacity of selected civil society groups. It presents the process of women’s empowerment in forest user groups by describing changes made in those groups once women begin participating and holding key decision-making positions. The findings note significant variation in funds allocated for social and community development activities, which are necessary to address the issues of poverty and social equity in Nepal. In addition, they note the importance of building both the capacity of individual women leaders and an enabling environment to support the women’s initiatives. A collaborative and inclusive approach that includes women and marginalized groups as committee executives and members of local government bodies is necessary to build the enabling environment.